Alternative Treatments for Premature Ejaculation: A Review of Pharmacological Strategies - Paula Bętkowska; Daria Krzyżanowska; Magdalena Strzelczyk; Iwona Koziołek; Joanna Wziątek; Gabriela Pabis; Wiktoria Fatyga; Patrycja Fatyga; Piotr Kowalik; Kinga Dowierciał (Quality in Sport, 2025)
Introduction and Purpose:Premature ejaculation (PE) is a common male sexual disorder with a complex etiology involving psychological, neurobiological, and physiological factors. PE is defined as ejaculation occurring earlier than desired, often causing distress. Its etiology is multifactorial and not fully understood. Current standard treatments such as Selective Serotonin Reuptake Inhibitors (SSRIs) and lidocaine-prilocaine creams are helpful but limited, prompting interest in alternatives. This review presents alternative pharmacological treatments for PE, excluding SSRIs and topical anesthetics, along with their side effects and benefits.